Far and away : a novel - Poeppel, Amy (Emily Bestler Books/Atria Books, 2025)
"Perfect strangers Lucy and Greta have agreed to a house swap--and boy, are they going to regret it. Lucy's hometown of Dallas has gone from home sweet home to vicious snake pit in the blink of an eye after her son makes a mistake he can't undo. And Greta's beloved flat in Berlin is suddenly up for grabs when her husband Otto takes a dream job in Texas without even telling her. In their rush to leave town, Lucy and Greta make a deal, pack their bags, and--thanks to martinis, desperation, and some very rusty German--have absolutely no idea what they're getting themselves into. Trading Southern charm and barbecue for European sophistication and schnitzel, the two women get a lot more than a change of scenery as they move into each other's houses, neighborhoods, and lives. Greta and Lucy's husbands are no help: Otto is winning over his colleagues, swimming laps in the backyard pool, and rooting for the Rangers, while Lucy's husband is doing a six-month stretch out west, either in a NASA biosphere or in jail, depending on who you ask. Meanwhile, Greta's daughter Emmi and Lucy's son Jack get tossed into each other's orbits, where they both discover secrets they can't ignore. When Greta's biggest career achievement--the buzzworthy purchase of a Vermeer at auction--is thrown into question and Lucy's past with a hot Viking named Bjørn invades her present, the two women need each other in ways they never could have imagined. Through jet lag, culture shock, suspiciously nice neighbors, and scandals that refuse to be left behind, Lucy and Greta will have to decide if they can ever go home again"--